Strategi Bersaing Hotel Syari’ah, Pendekatan Manajemen Bisnis Syari’ah: Studi Pada Syari’ah Hotel Solo - Azidni Rofiqo; Rahmani Timorita Yulianti (Islamic Economics Journal, 2019)
Islamic sharia is the only guide for people’s life of the sake of maqasid sharia fulfillment. Indonesia is now seeking a way to boost the sector of sharia tourism. One of the measurements taken to do so is through the enhancement of sharia hotel sector. However, unstable financial and political constraints are known to hamper the sustainability of sharia hotel. Sharia Hotel Solo is claimed to be the biggest sharia hotel in Indonesia. However, we need to analyze its position in Solo since the city is known to have a heightened hotel sector competition without being entailed by an increased level of consumer. Thus, this research is primarily aimed at describing the competitive strategy applied by Sharia Hotel Solo in accordance with sharia business management. In addition, it also unravels the strengths, weaknesses, opportunities, and threats of the hotel through sharia business management. The research was conducted through the quantitative method. It was analyzed through Internal-External Factor Evaluation, SWOT. The results of IFE show that hotel’s internal condition was very good as value of IFE in 3.55. The external condition of the hotel also very good as a result of EFE analysis in value of 3.29. However, I-EFE analysis reveals that Sharia Hotel Solo was situated in Cell I, indicating that its competitive strategy was located in developing and building. The SWOT analysis reveals that it can utilize the opportunity with its strength and overcome the threat by enhancing its strength. Penginapan Ciawi. (2020). Retrieved 21 May 2020, from http://www.penginapanciawi.my.id/